Islamic Republic of Iran : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This Selected Issues paper analyzes impediments to correspondent banking with the Islamic Republic of Iran. Even though international nuclear sanctions were lifted January 16, 2016, Iranian banks face protracted difficulties in reentering the international financial system through correspondent relationships with global banks. Significant challenges continue to prevent Iranian banks from fully reconnecting with global banks. These challenges relate mostly to remaining sanctions from the United States; the regulatory enforcement environment; and significant deficiencies in Iran's Anti-Money Laundering and Combating the Financing of Terrorism framework, including Iranian companies' lack of transparency. Domestic policy reforms can potentially facilitate reconnection to non-US global banks.